Structural equation modeling : - Pugesek, Bruce H. (Cambridge University Press, 2003)
Structural equation modeling (SEM) is a statistical methodology which, in this book, is applied to research questions in ecology and evolutionary biology. The book differs from others on SEM because it is written specifically for biologists with an approach that is adapted to their statistical knowledge and background. This text will serve as a valuable resource for both learning and teaching the SEM methodology. Data sets and programs that are presented in the book can also be downloaded from a web site to assist the learning process.